Multilevel system of social security (Economics and region, 2022)
The essence of social security as a priority component of national, in particular, economic security is revealed. It is determined that in the context of the aggravation of the current socio-economic crisis, the threats associated with COVID-19, the solution of social problems becomes even more important and relevant. A special threat in Ukraine is posed by the hybrid war, which has significantly affected the state of national security of Ukraine, in particular, human social security. Its negative consequences are both direct and indirect, which is a real social threat. The impact of hybrid warfare on human social security requires the substantiation of new, more effective mechanisms and tools for strengthening it. It is noted that the analysis and assessment of the state of social security should be systematic, comprehensive, assessing: the state of welfare and living standards; stability of social relations and organizational structure; the level of culture of society; availability of conditions for prevention and resolution of social conflicts; processes of desocialization of society, etc. t is emphasized that social security should be considered in the context of its multilevel system, in particular, it should be considered from the point of view of the economic level, namely: nano-, micro-, meso-, macro- and mega-level. The author's multilevel system of social security is offered, which includes five levels: human social security (nanoscale); social security of the business entity (micro level); social security of the region (meso level); social security of the state (macro level); global social security (megalevel). Author's definitions of the content (essence) of each level of social security and their functional components are given. In particular, human social security is defined as the degree (level) of protection of vital socio-economic interests of man (person), his rights, freedoms and values from internal and external, real and potential threats, and the functional components are: security of human life; security of realization of general social values; security of a decent standard of living; social security; psychological and mental security; self-defense; self-preservation; self-development, etc.
Keywords: national security; social security; human social security; threats; hybrid war; multilevel system; functional components